Grain boundary carbides as hydrogen diffusion barrier in a Fe-Ni alloy: A thermal desorption and modelling study. (15th December 2018) - Turk, Andrej; Bombač, David; Jelita Rydel, Jakub; Ziętara, Maciej; Rivera-Díaz-del-Castillo, Pedro E.J.; Galindo-Nava, Enrique I.
Abstract: A significant decrease in hydrogen absorption in the presence of grain boundary carbides compared to the carbide-free microstructure in the Ni-based HR6W alloy was measured by thermal desorption analysis (TDA). This novel observation is at odds with numerous existing reports – precipitate-rich microstructures generally absorb more hydrogen due to trapping effects. This discrepancy can only be explained by grain boundary diffusion which is known to be fast in Ni-based alloys. It is proposed that grain boundary diffusion is hindered by carbides, resulting in decreased hydrogen absorption. Further experimental evidence corroborates the hypothesis. In addition, a diffusion model was developed to quantify the experimental results, incorporating trapping, grain boundary diffusion and temperature effects. It was successfully applied to the reported TDA data as well as additional diffusion data from the literature. A parametric analysis showed that hydrogen absorption scales strongly with grain size and grain boundary diffusivity while grain boundary segregation energy has a much lower impact. The results of the study point at grain boundary precipitation as a possible means of hydrogen embrittlement mitigation in Ni alloys and austenitic stainless steels. Graphical Abstract: Highlights: Grain boundary carbides significantly reduce hydrogen absorption in a Fe-Ni alloy. A diffusion model accounting for grain boundary diffusion was developed. The model was used to predict and interpret the absorption behaviour in experiments. Carbides act as obstacles for otherwise fast diffusion along grain boundaries. It was shown that the model can be applied more generally to diffusion in Ni alloys.